Moisture management properties of knitted fabrics with varying structures and fibre content - Mohd Idris, Muhammad Khalis; Nasir, Siti Hana; Roslan, Mohd Nazrul (2024)
Heat stress can occur in high-intensity sports due to the high amounts of metabolic heat output. The heat released through the evaporation of water serves to lower the body's internal temperature, making sweating an important physiological process. Moisture management qualities, which allow for the rapid absorption and transport of water vapour and liquid perspiration from the skin to the outer surface of garments, are crucial in multilayer sportswear, as they allow for maximum wearer comfort. In this investigation, the moisture management qualities of knitted textiles used in the layers of athletic apparel were examined. The machine determines how much liquid moves through the fabric in all directions and on both sides. When compared to other fabric structures, R1 fabric was shown to have the highest liquid moisture management capacities, suggesting that it would be an excellent choice for the inner layer of sportswear due to its ability to wick perspiration away from the skin and into the garment. In this context, "Waterproof fabric" refers to fabrics S1, S2, and S3, while "Water repellent fabric" refers to fabric T1. Although fabrics of varying fibre content (S1, S2, and S3) showed similar moisture management properties, fabrics of varying structures showed varying values for dynamic liquid transfer. This shows that the fibre content of fabrics does not change depending on the fabric's ability to regulate moisture